Factors influencing people's knowledge, attitude, and practice in land use dynamics: A case study in Ca Mau province in the Mekong delta, Vietnam. (March 2018) - Tran, Hanh; Nguyen, Quoc; Kervyn, Matthieu
Highlights: Examining factors influencing the knowledge, attitude and practice of local households towards land use change programs. Education, Age, and Occupation are the main factors affecting their KAP of land use/cover change. Farmers are more willing to support LUCC programs, though less understanding due to lower education and communication. Increasing awareness through communication and education, especially for farmers, could be essential for LUCC management. Abstract: Land use is rapidly changing within the Mekong delta due to decisions of local actors. This study aims at understanding the factors influencing the understanding of inhabitants about the concepts, causes and effects of land use and cover changes (LUCC), as well as how they perceive and act about LUCC management. A Knowledge-Attitude-Practice (KAP) survey was carried out on a sample of 330 households in the Tran Van Thoi District, Ca Mau Province in the Mekong Delta, Vietnam. The respondents were surveyed on their knowledge of the conceptualization of LUCC, how LUCC are caused and what their consequences are. The results highlight the political, socio-demographic, economic and environmental causes and effects considered as meaningful by the respondents for understanding LUCC process. Multiple logistic regression (MLR) models with nested cross-validation were developed for investigating the factors influencing the knowledge, attitude and practice of individual households. Although variation exists in the significant predictors of the different K-A-P components, educational level, age, participation in group activity, access to communication mean, and occupation (farming or permanent employment) are shown to be the main influencing variables. The knowledge of the concept of LUCC, and to a lower extent of its causes and consequences, highly correlates with the Attitude and Practice regarding LUCC management, indicating the necessity of disseminating and enhancing LUCC understanding among local actors before implementing land use management projects.